An Aza resveratrol–chalcone derivative 6b protects mice against diabetic cardiomyopathy by alleviating inflammation and oxidative stress. Issue 3 (12th January 2018) - You, Shengban; Qian, Jianchang; Sun, Chuchu; Zhang, Hailing; Ye, Shiju; Chen, Taiwei; Xu, Zheng; Wang, Jingying; Huang, Weijian; Liang, Guang
Abstract: Inflammation and oxidative stress play a crucial role in the development of diabetic cardiomyopathy (DCM). We previously had synthesized an Aza resveratrol–chalcone derivative 6b, of which effectively suppressing lipopolysaccharide (LPS)‐induced inflammatory response in macrophages. This study aimed to investigate the potential protective effect of 6b on DCM and underlying mechanism. In H9c2 myocardial cells, 6b potently decreased high glucose (HG)‐induced cell fibrosis, hypertrophy and apoptosis, alleviating inflammatory response and oxidant stress. In STZ‐induced type 1 diabetic mice (STZ‐DM1), orally administration with 6b for 16 weeks significantly attenuated cardiac hypertrophy, apoptosis and fibrosis. The expression of inflammatory cytokines and oxidative stress biomarkers was also suppressed by 6b distinctly, without affecting blood glucose and body weight. The anti‐inflammatory and antioxidative activities of 6b were mechanistic associated with nuclear factor‐kappa B (NF‐κB) nucleus entry blockage and Nrf2 activation both in vitro and in vivo . The results indicated that 6b can be a promising cardioprotective agent in treatment of DCM via inhibiting inflammation and alleviating oxidative stress. This study also validated the important role of NF‐κB and Nrf2 taken in the pathogenesis of DCM, which could be therapeutic targets for diabetic comorbidities.